The Role of Law in Addressing Violence against Women and Children - Putri, Yumna Syaza Kani; Mahaputra, M Ridho (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Violence against women and children is a serious violation of human rights and is a complex and multidimensional social problem. This phenomenon not only reflects the failure of the legal system, but also shows the strong patriarchal culture that is still rooted in Indonesian society. Although there are various legal instruments such as Law No. 23 of 2004 concerning the Elimination of Domestic Violence, Law No. 35 of 2014 concerning Child Protection, and Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence, in reality violence is still rampant and even tends to increase every year. This study aims to analyze the role of law in overcoming violence against women and children, as well as to evaluate the effectiveness of the implementation of protection policies at the regional level. The method used is a normative legal approach with qualitative descriptive techniques, supplemented by field data and expert opinions to strengthen the analysis. The results of the study show that the implementation of the law still faces various obstacles, such as a lack of understanding of gender perspectives in law enforcement officers, minimal integrated protection services, and weak coordination between related institutions. Therefore, efforts are needed to strengthen institutions, provide legal education to the community, and have a more restorative and victim-oriented legal approach so that legal protection for women and children can run optimally.